Downscaling the grey water footprints of production and consumption. (20th September 2016) - Cazcarro, Ignacio; Duarte, Rosa; Sánchez-Chóliz, Julio
Abstract: While economic and environmental policies and strategies are largely designed at the international, national or regional level, the environmental impacts of these measures are often felt at a more geographically-localized level. In particular, the effects on water resources, especially regarding water pollution and water stress, are usually localized in very specific hotspots. In this work, we acknowledge these facts and attempt to identify the linkages among the 17 regions in Spain (a semi-arid country with significant geographical variations in water availability), the European Union (EU), and the Rest of the World (RW), while also looking at the local effects of those interactions. In particular, we study the grey water footprints (a measure of the assimilation capacity of water resources) of production, at both the regional and business level, with spatially explicit information, and the extension of those footprints throughout the supply chain, while also computing the water footprints of consumption at the regional level. This process is a combination of a detailed computation of grey water footprints from production, from agriculture (from diffuse pollution), and from more general economic activities (from point source pollution), with a multiregional input–output model that encompasses the 17 Spanish Regions, the EU, and the RW. We also identify hotspots and vulnerable areas, linking the grey water footprints from production originating in these areas to final-consumer responsibilities. As an example of the potential of the combined methodology, we design and evaluate the effects on grey water footprints of scenarios of import substitutions in Spain. Our results show strong final demand in regions such as Madrid and Catalonia, and in net exporting regions such as Andalusia, Aragon, Castile and Leon, Castile-La Mancha, Extremadura, and Navarre. Some of these regions contain areas that are clearly vulnerable to nitrates and other pollutants, and parts of these regions, most obviously in Andalusia and Extremadura, suffer water stress, which leads us to question the sustainability of the relationships between the structure of production and trade and the environment. Highlights: We model the grey virtual water interregional flows and footprints in Spain. The meso-economic input–output model is combined with GIS localized information. Vulnerable areas in the Castiles, Aragon and Andalusia are affected by production mostly destined to export. 21 of the 83 km 3 of grey WF from consumption in the Spanish regions come from other countries. We localize direct and indirect impacts of macro-meso scale changes as the level of imports changes.